If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 195 = 12 + x Solving 195 = 12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 195 + -1x = 12 + x + -1x Combine like terms: x + -1x = 0 195 + -1x = 12 + 0 195 + -1x = 12 Add '-195' to each side of the equation. 195 + -195 + -1x = 12 + -195 Combine like terms: 195 + -195 = 0 0 + -1x = 12 + -195 -1x = 12 + -195 Combine like terms: 12 + -195 = -183 -1x = -183 Divide each side by '-1'. x = 183 Simplifying x = 183
| 2y=103-x | | 5(x+5)+8(-x+8)=77 | | 3x-15+6x+1=45 | | -4(x-1)=9x+9 | | .5(10+12n)=.3333(15n+15) | | -4(x+6)=-4(x+2)-x | | 8(5c-1)-18=38c+8 | | -1=t+(-18) | | 8c^2-20c-12=0 | | 3.5(9)+3.5(9)+12(9)=180 | | 9x-6x-2=1 | | y=x^3-13x | | 7x+1=-2x+37 | | 6t+3(5t-4)=12(2t-2w) | | -16x-3=x-67 | | n^2+7.58333333333n=0 | | 6+3(5t-4)=12(2t-2w) | | 10x+-8=22 | | (4x-2)+(4x-2)+(x+3)+(x+3)=52 | | -2x(3x+9)=24 | | x+(-3*-8)=56 | | 3+(b+8)= | | y=(0-7)+6 | | y-115=5(x^2-50+625) | | 3(y-10)+1=3(y-8) | | -15v-40=23-8 | | 5x+1=12x-28 | | 17x-32+24x=134 | | 3.7+.25= | | -18+25=m-4 | | 192=(2x+2)(x-4) | | 11=12-6 |